A Semiotic Exploration of isiXhosa and Sesotho sa Leboa Literary Book Covers and Their Cultural and Religious Impact - Pocia, Thete, Igneciah; Anele, Gobodwana (Journal of Cultural Analysis and Social Change, 2025)
Readers buy books based on their cover designs, as the covers have a way of capturing the reader’s attention, and other readers choose them by choice, recommendations, or academic prescriptions. Scholars have analyzed book covers for intersemiotic interpretations; however, scholarly attention has been limited in exploring how books decode meaning and reflect cultural and religious significance. Book covers are used by authors as external objects of art or expressions of the artist’s artistic ideas to the readers. This paper has argued that book covers are not merely aesthetic elements but serve as rich sites of semiotic meaning-making. The aim was to analyze visual elements of isiXhosa and Sesotho sa Leboa’s literary book covers, exploring how graphics, colours, and typography convey deeper meanings to the readers. Additionally, it also sought to demonstrate how these elements reflect cultural and religious narratives that resonate with the target audience, and how these representations affect the reader’s perception and interpretation of texts. The qualitative method was adopted as the way and approach to data gathering, explored through textual analysis. The inspiration was drawn from Ferdinand de Saussure and Umberto Eco’s interpretations of the semiotic perspective. The findings of this paper have demonstrated that book covers serve as a medium for cultural and religious narratives and identity formation within the community. This paper’s findings indicated the influence and role played by visual elements on book covers. Lastly, this paper contributes to the scholarship of the significance of cover illustrations for book authors and publishers, emphasizing their embedded religious and cultural meanings.